A survey of major foliar and ear rot diseases in selected small-holder maize farms in KwaZulu-Natal and the Eastern Cape - Aveling, Terry A.S. (2026)
Dissertation (MSc Agric (Plant Pathology))--University of Pretoria, 2016.